Gambaran Perilaku Pekerja Dalam Mengurangi Paparan Debu Di Gudang Semen Conch Kota Baubau - La Ode Muhusari (Kampurui Jurnal Kesehatan Masyarakat, 2019)
The cement industry is one of the industries that growing rapidly, this are related to the total production capacity of cement factories which are spread in various regions of the archipelago reaching 27 million tons per year. Lung disease due to industrial dust has symptoms and signs that are similar to other lung diseases that are not caused by dust in the work environment. The purpose of this study was to determine the behavior of workers in reducing dust exposure in Baubau Conch cement warehouse. This type of research is a quantitative study with a descriptive approach to describing the behavior of workers in reducing dust exposure in Baubau conch cement wareho use. The number of samples in this study is the population chosen as the sample. The technique of determining the sample by using total sampling, so that the total sample of 20 respondents. Data obtained using questionnaires and observations, then processed using SPSS version 22. Analysis of the data used is univariate analysis.The results of this study indicate that of the 20 respondents studied, respondents who included sufficient knowledge were 15 (75.0%), and less than 5 (25.0%), positive attitudes were 19 (95.0%) and negative ones were 1 (5.0%) and Fair Action as many as 8 (40.0%), and less than 12 (60.0%).The conclusion of this study is that there is sufficient knowledge and a positive attitude towards reducing dust exposure, but the actions that workers have are still lacking in reducing dust exposure. It is recommended for cement transport workers to wear Personal Protective Equipment that meets the requirements while working so as to prevent diseases that can arise due to exposure to cement dust.